PENDEKATAN RULE OF REASON DALAM KETERLAMBATAN PENGAMBILALIHAN SAHAM - Rosidin, Utang; Jaelani, Elan; M, Rifa Laila Syarifatul (Gapenas Publisher, 2024)
The delay in taking these shares is due to unhealthy business practices or monopolistic practices with a rule of visible reason approach. So look objectively at whether the Commission's decision in the case of unfair trade competition is based on Law Number 5 of 1999 concerning Monopolies and Unfair Business Competition and impose sanctions in the form of fines on economic entities that do not notify such notification as the acquisition of shares, as exemplified in the alleged case delay in taking over the shares of PT Mitra Keluarga Karyasehat Tbk in PT Bina Husada Gemilang (Number 12/KPPU-M/2022). This legal research uses a normative juridical method. This decision confirms to law enforcers the violation of unfair business competition that results in market losses in healthily doing business